Enhancing functional recovery for young people recovering from first episode psychosis via sport-based life skills training: outcomes of a feasibility and pilot study. Issue 1 (31st December 2022) - Brooke, Lauren E.; Gucciardi, Daniel F.; Ntoumanis, Nikos; Chapman, Michael T.; Lines, Robin L. J.; Perry, Yael; Gilbey, Dylan; Formby, Tegan; Phillips, Toby; Lin, Ashleigh
ABSTRACT: Early intervention within First Episode Psychosis (FEP) recovery efforts support functional recovery in several ways, including increasing levels of (1) physical activity (2) life skills, and (3) social connectivity. Sport has been proposed as an ideal platform to target these three goals simultaneously. The primary aims were to assess the feasibility of utilising sport-based life skills within FEP recovery efforts and test intervention components. The secondary aim was to evaluate the potential recovery benefits. Seven young people (aged 15–25 years) with FEP participated in a six-week sport programme alongside their support workers (community and peer workers) from the service, including peer workers with a lived experience of psychosis. The programme consisted of various sporting activities, which were designed to promote physical activity, maximise social connectivity, and teach life-skills (e.g. motivation, emotional regulation, and goal-setting) that are relevant and transferrable to other contexts (e.g. school, employment, independent living). The support participants engaged with the programme at the same level as the young people, with the role of providing support and normalising/modelling engagement. The young and support participants provided feedback during and after the programme via questionnaires and interviews. Young participants self-reported physical activity levels, psychological needs, recovery dimensions, and life skills pre- and post- intervention using established psychometric tools. We used thematic analysis to analyse the qualitative data and compared this information with other data collected (e.g. attendance, feedback, quantitative measurements). The study culminated with a process evaluation. The results indicated that, despite challenges with engagement for young people with FEP, sport-based life skills programming may be a feasible and useful recovery outlet. In addition, the results highlighted specific intervention components that were useful to promote engagement and recovery benefits. This study serves as a critical foundation for future sport-based work within FEP recovery.